2021
DOI: 10.1177/0890117121992292
|View full text |Cite
|
Sign up to set email alerts
|

College Students’ Reasons for Using JUULs

Abstract: Purpose: To identify reasons that college students use JUUL and explore associations between reasons for using JUUL and social and behavioral (tobacco use) factors. Design: On-line, cross-sectional survey. Setting: Large southwestern university in the US. Subjects: Undergraduate students (n = 605) who owned JUUL and used it weekly. Measures: The study measured age of JUUL initiation, JUUL dependence, and use of other e-cigarettes and other tobacco products. Participants described reasons for JUUL use as brief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Variability was reported using Nagelkerke R. 2 Finally, open-ended responses were analyzed by grouping similar responses together into categories, a technique used in prior research that explored responses to an open-ended item. 32 , 33 …”
Section: Methodsmentioning
confidence: 99%
“…Variability was reported using Nagelkerke R. 2 Finally, open-ended responses were analyzed by grouping similar responses together into categories, a technique used in prior research that explored responses to an open-ended item. 32 , 33 …”
Section: Methodsmentioning
confidence: 99%
“…(1, 2) Common used devices include JUUL, as well as Puff bar, which come with disposable pods. (3,4) When asked, users reported reasons for the use of vapes/e-cigarettes is to replace smoking, not the same as smoking, and/or being marketed as being a healthier option due to the absence of carbon monoxide production. (3) The American Thoracic Society (ATS) has reported that the measurement of Fractional of Exhaled Nitric Oxide (FeNO) is simple and can be used as a biomarker in the assessment and management of airways disease.…”
Section: To the Editormentioning
confidence: 99%
“…(3,4) When asked, users reported reasons for the use of vapes/e-cigarettes is to replace smoking, not the same as smoking, and/or being marketed as being a healthier option due to the absence of carbon monoxide production. (3) The American Thoracic Society (ATS) has reported that the measurement of Fractional of Exhaled Nitric Oxide (FeNO) is simple and can be used as a biomarker in the assessment and management of airways disease. (5) The change in FeNO due to inflammatory responses seen in the airway fluctuates from breath to breath, making repetitive sample collection crucial for accuracy, yet recent studies involving measurements of airway inflammation using FeNO with e-cigarettes have shown mixed results.…”
Section: To the Editormentioning
confidence: 99%
“…Common reasons for using e-cigarettes among young people include but are not limited to taste, entertainment, experimentation, social influence, replacement of tobacco cigarettes, curbing cravings, and/or addiction (Evans-Polce et al, 2018;Newcombe et al, 2021;Khouja, Taylor, and Munafò, 2020). Young people may also consider e-cigarettes a good alternative to conventional tobacco cigarettes, as they are cheaper and thought to contain less toxins than tobacco cigarettes (Etter and Bullen, 2011).…”
Section: Introductionmentioning
confidence: 99%